(untitled) (Journal of the College of Basic Education, 2022)
The world today is witnessing a continuous development that cannot be comprehended by learning programs and methods, which necessitates the existence of programs that enable the learner to develop motor skills in order to develop his capabilities and capabilities in response to his inclinations and desires. The experimental method was used, with the design of the two equal experimental groups, on a sample of (30) juniors who were randomly selected from among the football school players at the age of (14) years for the sports season 2021/2022. Simulation is of great importance in developing passing and shooting skills for junior footballers, and researchers have recommended the use of exercises specific Symmetrical and oriented to the brain in developing passing and shooting skills for junior footballers.